EVALUASI PELAKSANAAN BANTUAN SOSIAL KELOMPOK USAHA BERSAMA (KUBE) PADA MASYARAKAT MISKIN DI KECAMATAN KARANGASEM - Aryantini, Ni Luh Kade Manik Indah; Purbadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 9 (2020): VOL 9 NO 9, SEPTEMBER 2020 (1888-2151), 2020)
Poverty is marked by the low income of the people. To improve the level of income, community empowerment needs to be done such as the KUBE Social Assistance Program. The purpose of this research is to find out 1) the effectiveness of KUBE social assistance program as seen from the input, process and output indicators, 2) the level of income of the poor after the KUBE social assistance program is implemented, 3) the weaknesses that are found in the KUBE social assistance program. This research was conducted in Karangasem District, a sample of 75 respondents and a purposive sampling technique. This research uses descriptive statistical test, statistical inference test, that is Wilcoxon different test. The results of this study are the success rate of the KUBE social assistance program seen from the input variables, process variables, and output variables in Karangasem Subdistrict classified as very effective. The income of the KUBE social assistance recipients increased after the KUBE social assistance program was implemented. Weaknesses in the KUBE social assistance program funds the amount of assistance that is felt still less by some groups KUBE.   Keywords: Evaluation, Effectiveness, KUBE, and Revenue